Revolutionizing urban solid waste management with AI and IoT: A review of smart solutions for waste collection, sorting, and recycling - Abderrahim Lakhouit (Results in Engineering)
This review explores the transformative impact of artificial intelligence (AI) and the Internet of Things (IoT) on urban solid waste management, focusing on their potential to enhance the processes of waste collection, sorting, and recycling. With urban populations on the rise and waste generation rapidly increasing, cities face critical challenges to environmental sustainability and public health. The integration of IoT-based smart waste management enables municipalities to utilize real-time data to analyze waste flow, predict generation trends, and improve operational efficiency. AI-powered sorting systems and advanced robotics can further optimize recycling rates by reducing the need for manual labor and increasing material recovery in recycling facilities.Additionally, the necessity to leverage strong collaboration among governments, technology providers, and the public is emphasized in this paper as a means to develop effective policy frameworks and foster community engagement in sustainable waste practices. The review also addresses challenges such as high initial costs, privacy concerns, and technical limitations, advocating for continued investment in innovative technologies and robust data privacy solutions. Ultimately, this research promotes a holistic approach to sustainable waste management that centers on building a circular economy and reducing environmental impacts. By adopting AI and I oT advanced technologies, cities can achieve their sustainability objectives, thereby paving the way for cleaner, more resilient urban environments that will benefit both current and future generations.